Developmentally Regulated Telomerase Activity Is Correlated with Chromosomal Healing during Chromatin Diminution in Ascaris suum - Magnenat, Laurent (American Society for Microbiology, 1999)
Telomerase is the ribonucleoprotein complex responsible for the maintenance of the physical ends, or telomeres, of most eukaryotic chromosomes. In this study, telomerase activity has been identified in cell extracts from the nematode Ascaris suum. This parasitic nematode is particularly suited as a model system for the study of telomerase, because it shows the phenomenon of chromatin diminution, consisting of developmentally programmed chromosomal breakage, DNA elimination, and new telomere formation. In vitro, the A. suum telomerase is capable of efficiently recognizing and elongating nontelomeric primers with nematode-specific telomere repeats by using limited homology at the 3′ end of the DNA to anneal with the putative telomerase RNA template. The activity of this enzyme is developmentally regulated, and it correlates temporally with the phenomenon of chromatin diminution. It is up-regulated during the first two rounds of embryonic cell divisions, to reach a peak in 4-cell-stage embryos, when three presomatic blastomeres prepare for chromatin diminution. The activity remains high until the beginning of gastrulation, when the last of the presomatic cells undergoes chromatin diminution, and then constantly decreases during further development. In summary, our data strongly argue for a role of this enzyme in chromosome healing during the process of chromatin diminution.